2001
DOI: 10.1034/j.1601-0825.2001.70405.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligodontia is associated with extra‐oral ectodermal symptoms and low whole salivary flow rates

Abstract: Thirty-nine (57%) of the oligodontia patients had disturbances in either hair, nails and/or sweat production in addition to teeth and were classified as the ED group. The remaining 29 oligodontia patients had no obvious signs of EDs (non-ED group). The prevalences of dry skin, asthma and eczema were higher, and whole salivary secretory rates lower, in the ED group as compared to the control group. Intermediate values were observed in the non-ED group. Incisors, canines and molars were more frequently missing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
32
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 21 publications
(21 reference statements)
6
32
0
8
Order By: Relevance
“…HED patients demonstrate reduced whole saliva flow (Nordgarden et al, 2001) leading to xerostomia (dry mouth), further damage to an already compromised dentition and a reduced quality of life. Mammals have three pairs of major SGs that produce approximately 90% of total saliva (reviewed in Tucker, 2007): the submandibular (SMG) and sublingual (SLG) glands, situated under the tongue with ducts secreting into the floor of the mouth, and the parotid at the back of the mouth in between the upper and lower jaw, with ducts secreting saliva into the inner cheek.…”
Section: Introductionmentioning
confidence: 99%
“…HED patients demonstrate reduced whole saliva flow (Nordgarden et al, 2001) leading to xerostomia (dry mouth), further damage to an already compromised dentition and a reduced quality of life. Mammals have three pairs of major SGs that produce approximately 90% of total saliva (reviewed in Tucker, 2007): the submandibular (SMG) and sublingual (SLG) glands, situated under the tongue with ducts secreting into the floor of the mouth, and the parotid at the back of the mouth in between the upper and lower jaw, with ducts secreting saliva into the inner cheek.…”
Section: Introductionmentioning
confidence: 99%
“…The mean number of teeth missing from agenesis in this group was identical to individuals who did not report ectodermal symptoms. In studies of individuals with oligodontia referred to specialist dental centers, 29% of patients were reported to have a heritable syndrome diagnosed by a medical specialist [Schalk-van der Weide et al, 1994], and 57% to have clinical symptoms from hair, nails, and sweat glands [Nordgarden et al, 2001]. This implied that improved clinical diagnostics in dentistry through the identification of extra-oral symptoms could help to identify individuals with for example, ED among individuals with oligodontia.…”
mentioning
confidence: 96%
“…Thus, in 46% of patients a syndrome was confirmed or could not be excluded. A Norwegian study found 57% of individuals with oligodontia to have disturbances in hair, nails, or sweat production [Nordgarden et al, 2001]. These studies inferred that ectodermal symptoms and ectodermal dysplasias (EDs) are more common in individuals with oligodontia than was previously anticipated.…”
mentioning
confidence: 97%
“…Hyposalivation leads to microbial infections as well as difficulty in chewing, speaking, and swallowing (Gupta et al 2006). Reduced saliva output is commonly seen in the following circumstances: a) Sjögren syndrome, b) head and neck γ-irradiation, c) trauma of the salivary glands, and d) developmental disorders such as ectodermal dysplasias (Nordgarden et al 2001;Konings et al 2005;Gupta et al 2006;Rogus-Pulia and Logemann 2011). Current treatments for hyposalivation are more palliative than curative.…”
Section: Introductionmentioning
confidence: 99%